ORGANISATIONAL BEHAVIOR - Creed, Andrew. (OXFORD UNIVERSITY PRESS, 2011)
People and their relationships define the contemporary workplace. Using an integrated approach, this text provides deep insight into significant organisational behaviour topics and provides an essential introduction to the subject.